Application of numerical model Simclast for studying the development of Red river delta in late Pleistocene-Holocene - Dong, Mai Duc; Phach, Phung Van; Thanh, Nguyen Trung; Hung, Duong Quoc; Hiep, Pham Quoc; Diep, Nguyen Van; Shakirov, Renat (Vietnam Journal of Marine Science and Technology, 2020)
The Simclast model has been verified and applied effectively in simulating the delta development for some major deltas in the world. In this study, we applied the model Simclast for simulating the history of the Red river delta development in late Pleistocene-Holocene. Results of the model reveal that the mainland of study area had reduced rapidly during transgression period (10,000-8,000 BP). The morphology changed significantly in the paleo-Red and Day river systems, but slightly in the paleo Thai Binh river system. The paleo-river network had been active in upper part before 11,000 BP and then shifted seaward until 2,000 BP. The river-sea interaction causes erosion and accumulation; as a result the morphology changed remarkably. The paleo-Thai Binh river had been inactive until 5,500 BP and then it was active but the morphology had not varied remarkably. The recent coastline generated from Simclast is relatively in accordance with the present coastline.